Full-scale validation of FE models for geometrically imperfect flange connections. (December 2021) - Seidel, Marc; Stang, Andre; Wegener, Filip; Schierl, Christopher; Schaumann, Peter
Abstract: Geometrical imperfections are an important aspect for fatigue design of bolted ring flange connections, particularly for support structures of wind turbines. This paper deals with the validation of 3D FEA models including such imperfections. Measurements from a 1.5 MW onshore wind turbine tower are compared against numerical results from two independently built FE models. The results show that the effect of imperfections, which have only been measured at the tower manufacturer, can be qualitatively well predicted by the FEA model. Furthermore, the results from the two completely independent models are almost identical, giving confidence that results can be reproduced. Recommendations for building FEA models are given, such that designers wishing to use idealized or measured imperfections for design purposes have guidance. Highlights: Measured ring-flange load-transfer function with inside and outside strain gauges at the tower wall Independently developed FE-models of the measured ring-flange connection with detailed flange-imperfection modelling Validation of the finite-element models based on agreement between modelled and measured load-transfer functions